Isolation and characterization of ZK002, a novel dual function snake venom protein from Deinagkistrodon acutus with anti-angiogenic and anti-inflammatory properties - Chan, Brandon Dow; Wong, Wing-Yan; Lee, Magnolia Muk-Lan; Yue, Patrick Ying-Kit; Dai, Xiangrong; Tsim, Karl Wah-Keung; Hsiao, Wen-Luan Wendy; Li, Mandy; Li, Xiao-Yi; Tai, William Chi-Shing (Frontiers in Pharmacology, 2023)
Introduction: Pathological angiogenesis, the abnormal or excessive generation of blood vessels, plays an important role in many diseases including cancer, diabetic retinopathy, psoriasis, and arthritis. Additionally, increasing evidence supports the close linkage between angiogenesis and inflammation. Snake venoms are a rich natural source of biologically active molecules and carry rich potential for the discovery of anti-angiogenic and anti-inflammatory modulators. Methods: Here, we isolated and purified a novel protein, ZK002, from the venom of the snake Deinagkistrodon acutus, and investigated its anti-angiogenic and anti-inflammatory activities and mechanisms. Results: ZK002 was identified as a 30 kDa heterodimeric protein of α and β chains, which exhibited anti-angiogenic activity in various in vitro assays. Mechanistically, ZK002 inhibited activation of VEGF signaling and related mediators including eNOS, p38, LIMK, and HSP27. ZK002 also upregulated the metalloproteinase inhibitor TIMP3 and inhibited components of the VEGF-induced signaling cascade, PPP3R2 and SH2D2A. The anti-angiogenic activity of ZK002 was confirmed in multiple in vivo models. ZK002 could also inhibit the in vitro expression of pro-inflammatory cytokines, as well as in vivo inflammation in the carrageenin-induced edema rat model. Conclusion: Our findings highlight the potential for further development of ZK002 as a dual function therapeutic against diseases with involvement of pathogenic angiogenesis and chronic inflammation.